Sustainability/resilience of soil organic matter components in an Argentinean arid region - Vázquez, Carolina; Merlo, Carolina; Noe, Laura Belén; Romero, Carlos; Abril, Adriana; Carranza, Carlos (Centro SECS de Documentación en Ciencias del Suelo (Ce.SECS), 2024)
This short communication presents a novel approach to determining the soil sustainability of productive practices in an Argentinean arid region, using the resilience degree of soil organic matter components. The study was conducted in four sites of the Arid Chaco region of the Cordoba province: one undisturbed site, two sites with livestock (with total and with selective clearing) and one site with agriculture. In each site three soil samples were taken and total soil organic matter, fulvic and humic acids, and non-humic substances were analyzed. Variations of each component (%) between each productive practice and the undisturbed site were calculated in order to establish the resilience degree. The livestock soils showed: a) moderate resilience for non-humic substances, b) low resilience for organic matter and humic acids, and c) no resilience for fulvic acids. The agricultural soils showed: a) low resilience for total organic matter and non-humic substances, and b) no resilience for fulvic and humic acids. We conclude that this approach is a powerful tool for establishing management practices according to each particular situation, allowing improved productivity in arid regions.